Structured Implementation of Social–Emotional Learning for Children with Special Needs: Implementasi Terstruktur Pembelajaran Sosial Emosional bagi Anak Berkebutuhan Khusus - Handayani, Auliya Kartika; Mahabbati, Aini (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Social–emotional development is a fundamental domain in early childhood education that shapes children's ability to interact, self-regulate, and build empathy. Specific background: Children with special needs require targeted strategies and structured programs to develop social–emotional competencies within inclusive settings. Knowledge gap: Although various kindergartens have implemented social–emotional programs, limited studies detail their classroom-level application using the CASEL framework. Aims: This study explores how Al-Ikhlas Kindergarten implements social–emotional learning (SEL) for children with special needs through instructional, integrative, and participatory approaches. Results: Findings reveal that teachers apply explicit instruction, integrate SEL values across learning components, and involve students in classroom leadership, decision-making, and problem-solving. The process strengthens empathy, cooperation, and self-control among students. Novelty: The study highlights a contextualized model of SEL implementation in early childhood inclusive education grounded in the CASEL indicators. Implications: The results emphasize the need for teacher training and structured planning to optimize social–emotional competencies among children with special needs in inclusive classrooms. Highlights Explicit instruction supports the social–emotional growth of children with special needs. Integration of SEL principles into learning promotes inclusive and meaningful classroom interaction. Student participation develops leadership, empathy, and collaboration skills. Keywords Social Emotional Learning, Children With Special Needs, Early Childhood Education, Inclusive Classroom, CASEL Framework